Experimental investigations on wall pressure in suddenly enlarged ducts at supersonic Mach number regimes - Baig, Maugal Ahmed Ali; Khan, Sher Afghan; Rathakrishnan, E. (rspublication, 2012)
This paper presents the results of an experimental work carried out to find the wall pressure distribution in a suddenly enlarged duct. The enlarged duct is attached to the exit of a convergent- divergent axisymmetric nozzle. The area ratio (i.e. ratio between cross sectional arean of the sudden expansion duct and the nozzle exit area) considered in the present study is 4.84. The supersonic Mach number regimes considered in the present study are 1.87, 2.2 and 2.58. The length to diameter ratio is 4. The nozzle pressure ratio (NPR) used is 3, 5, 7, 9, and 11 for all the Mach numbers. An active control method in the form of Microjets is used to control the base pressure. The prime investigations are towards finding the effect of Microjets on wall pressure for above said parametric conditions. It is found that for area ratio 4.84 the Microjets which are used as active control method for base pressure, does not adversely affect the wall pressure,contradicting the peculiar oscillatory nature in the enlarged duct when controls are employed.